The Assessment on Synergistic Activity of Ebselen and Silver Ion Against Yersinia pseudotuberculosis - Dong, Chuanjiang; Chen, Wei; Zou, Lili; Liu, Binbin; Deng, Kaihong; Guo, Dingrui; Wang, Peng; Chen, Hao; Wang, Helen; Wang, Jun (Frontiers in Microbiology, 2022)
Yersinia pseudotuberculosis is a foodborne zoonotic bacterium that is pathogenic to guinea pigs, rabbits, and mice. It also causes pseudotuberculosis in humans. However, it still lacked the scientific basis for control. Here, we found out that Ebselen (EbSe) exhibited synergistic antibacterial activity with silver nitrate (Ag+) against Y. pseudotuberculosis YpIII strain with high efficacy in vitro using UV-vis, DTNB, LSCM, FCM, ETM and WB assays. The depletion of total glutathione (GSH) amount and inhibition of thioredoxin reductase (TrxR) activity in thiol-dependent redox system revealed the destructiveness of EbSe-Ag+-caused intracellular oxidative stress. Furthermore, a YpIII-caused mice gastroenteritis model was constructed, and EbSe-Ag+ significantly reduced bacterial loads with low toxicity, down-regulated the expression levels of interferon (IL)-1β and tumor necrosis factor-α, up-regulated the expression level of IL-10 on-site, demonstrating the in vivo antibacterial activity and immune-modulatory property of EbSe-Ag+. Collectively, these results provided academic fundament for further analysis and development of EbSe-Ag+ as the antibacterial agents for pseudotuberculosis control.